Oral Zinc Sulfate for Prevention and Treatment of Chemotherapy-Induced Oral Mucositis: A Meta-Analysis of Five Randomized Controlled Trials - Tian, Xu; Liu, Xiao-Ling; Pi, Yuan-Ping; Chen, Hui; Chen, Wei-Qing (Frontiers in Oncology, 2018)
Aims: Chemotherapy-induced oral mucositis is an extremely serious complication faced by cancer patients. The role of oral zinc sulfate in preventing and treating chemotherapy-induced oral mucositis remains debate. Objectives: The aim of this systematic review is to assess the potential of oral zinc sulfate for this morbid condition. Methods: A systematic search was conducted electronically in PubMed, EMBASE, and Cochrane Central Register of Controlled Trials (CENTRAL) to capture all potential randomized controlled trials investigating the efficacy and safety of oral zinc sulfate in prevention and treatment of chemotherapy-induced oral mucositis, and the retrieval time was limited from their inception to April 2018. We assigned 2 independent investigators to perform search, screen citations, extract information, and evaluate the risk of bias of all included trials. And then, RevMan 5.3 software was utilized to perform all statistical analyses. Results: We included five eligible studies eventually, in which 352 patients were analyzed. Meta-analysis based on limited data revealed that oral zinc sulfate did not decrease the incidence of chemotherapy-induced oral mucositis (RR [relative risk] = 0.52, 95% CI [confidence interval] = 0.17 to 1.64) and not relieve the chemotherapy-induced oral mucositits grade (RR = 0.62, 95% CI = 0.11 to 3.56; RR = 0.70, 95% CI = 0.29 to 1.71). Moreover, qualitative analysis suggested that oral zinc sulfate can also not significantly reduce the oral pain intensity, delay onset of chemotherapy-induced oral mucositis, decrease adverse events and improve quality of life compared to control regimes. Conclusions: Oral zinc sulfate may provide no clinical benefits in preventing or reducing the incidence, severity, and pain intensity in cancer patients. However, due to the presence of limitations, we still suggest designing further studies with large-scale and rigorous methods of addressing data to investigate the effects and safety of oral zinc sulfate for this pathologic condition.